Chemical Specifications for Raw Materials Used in The Kufa Cement Industry in Iraq - Al-Naffakh, Jameel; Al-Fahham, Mohammed; Jafar, Israa (International Journal of Environment, Engineering and Education, 2020)
This paper aims to provide background information on raw materials included in the cement industry that have chemically examined. The raw materials entering the factory examined, which include stone, crude oil, iron dust, sand, and gypsum, as it found that the total carbonate ratio is 89 percent as a weight ratio and the sulfide is smaller or equal to 1 percent as a weight ratio, and the magnesium carbonate is smaller or equal to 3 percent. For iron dust with sand, the total carbonates of the mixture were smaller or equal to 85 percent, and magnesium carbonate was smaller or equal to 3 percent. Silica oxide also examined in the sand were the results of the examination were greater than 85 percent. For sulfide oxide smaller than 1 percent, as well as for iron dust, the proportion of oxide Ferric is higher than 55 percent, the percentage of alumina oxide is less than 10 percent, silica oxide is less than 20 percent, as well as for crude oil, as it contains less than 4 percent of sulfide oxide, as well as primary and secondary gypsum examination, and it found that sulfide oxide is greater than 31 percent if the gypsum is Secondary and greater than 42 percent if the gypsum is primary. Materials are non-soluble smaller than 8 percent if it was secondary gypsum and less than 5 percent if the primary gypsum. Where these models examined and analyzed, and the storage location of the models examined was determined.